1995
DOI: 10.1113/jphysiol.1995.sp020870
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Na(+)‐H+ exchange by altered cell volume in perfused rat mandibular salivary gland.

Abstract: Manchester M13 9PT, UK 1. Intracellular pH (pH1) was measured by spectrofluorometry in perfused mandibular salivary glands isolated from the rat and loaded with the pH-sensitive fluoroprobe 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein (BCECF). Cell volume changes were estimated from changes in intracellular water content measured by proton NMR spectroscopy.2. Stimulation with 1 ,UM acetylcholine (ACh) led to a 15 + 2% decrease in cell volume. A transient decrease in pH1 was followed by a sustained increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous in vitro studies in mouse parotid acinar cells directly established that NHE1 is the Na ϩ /H ϩ exchanger isoform up-regulated by muscarinic receptor stimulation (29) and thus is the exchanger most likely to have a major role in modulating the rate of secretion (23,35,36). The present in vivo functional studies revealed that the knockout of Nhe1 gene expression inhibited pilocarpine-induced salivary flow, with the magnitude of the inhibition increasing during sustained stimulation.…”
Section: Discussionmentioning
confidence: 56%
“…Previous in vitro studies in mouse parotid acinar cells directly established that NHE1 is the Na ϩ /H ϩ exchanger isoform up-regulated by muscarinic receptor stimulation (29) and thus is the exchanger most likely to have a major role in modulating the rate of secretion (23,35,36). The present in vivo functional studies revealed that the knockout of Nhe1 gene expression inhibited pilocarpine-induced salivary flow, with the magnitude of the inhibition increasing during sustained stimulation.…”
Section: Discussionmentioning
confidence: 56%
“…8). This contrasts with other mammalian salivary glands in which a shift in the pH activation curve of the exchanger enables it to maintain H+ extrusion at elevated values of pH, (Manganel & Turner, 1989;Steward et al 1989;Okada et al 1991;Seo et al 1995). From this we conclude that, in the sheep parotid, where pHi rises above the resting level during sustained stimulation, the Na+-H+ exchanger is unlikely to be any more active than in the resting condition and may indeed be less active.…”
Section: Inhibitors Of Na`-h+ Exchangementioning
confidence: 55%
“…Therefore, when possible, it is important to verify findings made by immunostaining with additional independent techniques such as RT‐PCR analysis and measurement of activity, as reported here. Hence, based on our combined findings we conclude that SMG acinar cells express only NHE1 in the BLM, which probably mediates the acetylcholine‐ and cell shrinkage‐mediated, amiloride‐sensitive alkalization in these cells (Seo et al 1995).…”
Section: Discussionmentioning
confidence: 76%